Osteoprogenitor cells from non-regenerative bone show greater resistance to cellular stress than those from regenerative bone - Broussard, Joshua; Culpepper, Sylvia; Long, Tyrel; Trostle, Alexander J.; Tower, Robert J.; Sammarco, Mimi C.; Simkin, Jennifer (Frontiers in Cell and Developmental Biology, 2025)
IntroductionBone regeneration following injury depends on osteoprogenitor cells derived predominantly from the periosteum. Incomplete regeneration has been attributed to both cell-extrinsic factors (e.g., environment, inflammation, mechanical instability) and cell-intrinsic factors (e.g., impaired proliferation or differentiation of stem cells). In the digit amputation mouse model, amputation through the third phalanx (P3) supports complete regeneration, while amputation through the second phalanx (P2) results in callus formation and scarring. Periosteal cells are known to be the major contributing cell source for repair and regeneration. Yet the healing outcomes of P2 and P3 amputations are significantly different. This study tests whether P2 and P3 cells are functionally equivalent.Methods and resultsUsing in vitro cellular stress tests, we compared the intrinsic properties of periosteal cells from P2 and P3 bones and found that P3 periosteal cells were more prone to proliferative senescence and less resistant to cellular stress in vitro than those from P2. In vivo, senescent cells were detected at both P2 and P3 injury sites, but their senescence-associated secretory phenotypes (SASPs) differed depending on the amputation level. Specifically, P2 cells expressed higher levels of pro-inflammatory cytokines (e.g. Tnf, Il1b) whereas P3 cells expressed higher levels of protease inhibitors (e.g. Serpine1, Timp2).DiscussionTogether, these findings suggest that periosteal cells exhibit intrinsic differences based on anatomical location, which may influence their regenerative capacity and contribute to different healing outcomes.